2010
DOI: 10.1111/j.1600-0765.2008.01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of elastin, fibrillins and microfibril-associated glycoprotein-1 in the developing periodontal ligament of the rat molar

Abstract: Elastin expressed in the periodontal ligament assembled into elaunin fibers in the vicinity of blood vessels. Both fibrillin-2 and MAGP-1 are structural components not only of the elastin-associated microfibrils but also of elastin-free microfibrils, with possible roles in elastogenesis and in periodontal ligament homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…In our previous immunohistochemical study in rodent molar periodontal ligament, no evidence was found for the presence of fibrillin-1 (Sugawara et al 2010). The results of the present study clearly showed that monkey molar tooth periodontal ligament contained both fibrillin-1 and fibrillin-2, and that the pattern of distribution of fibers positive for these macromolecules was basically the same as that of oxytalan fibers.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…In our previous immunohistochemical study in rodent molar periodontal ligament, no evidence was found for the presence of fibrillin-1 (Sugawara et al 2010). The results of the present study clearly showed that monkey molar tooth periodontal ligament contained both fibrillin-1 and fibrillin-2, and that the pattern of distribution of fibers positive for these macromolecules was basically the same as that of oxytalan fibers.…”
Section: Discussioncontrasting
confidence: 48%
“…In view of the close spatial relationship of oxytalan fibers to blood vessels, the concept that oxytalan fibers act as a mechanoreceptive system is particularly compelling (Sims 1975;Chantawiboonchai et al 1998;Tashiro et al 2002;Sawada et al 2006;Sugawara et al 2010). In the periodontal ligament of continuously erupting rat incisor, it has also been suggested that oxytalan fibers provide guidance for the migration of fibroblasts (Beertsen et al 1974), although direct evidence to support this hypothesis is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a possibility that elastin in supraspinatus tendon is cross-linked or modified in a manner which renders it difficult to extract or insoluble. However, one theory worth exploring is that fibrillin-microfibrils in supraspinatus tendon are elastin-free, similarly to the ones described in the periodontal ligament [38]. An in situ hybridization study of the localised expression of ECM components in healing supraspinatus tendon in the rat has found elastin to be present only in blood vessels [39], and a recent study in the horse superficial digital flexor tendon has shown elastin was predominantly localised to the interfascicular matrix [40], whilst it is well established that fibrillin-rich microfibrils are regularly interspersed throughout the fascicular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Using immunohistocheminal analysis in the rat [26] and immunoelectron analysis in the monkey [23], it has been demonstrated that oxytalan fibers in the PDL are associated with fibrillin-1 and fibrillin-2. Our series of studies have shown that human PDL fibroblasts express both fibrillins and produce a network of oxytalan fibers associated with them [2729].…”
Section: Introductionmentioning
confidence: 99%